Subependymal Cysts and Biotin Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Subependymal cysts were identified by cranial ultrasound and confirmed by MRI in an infant with holocarboxylase synthetase (HCS) deficiency, presenting with lactic acidosis, shock, and hypertonia, and responsive to biotin therapy (10mg daily), in a report from Devos Children's Hospital, Grand Rapids, MI.